SMCis: Scientific Applications Monitoring Tool for HPC Environments - Silva, Gabrieli; Klôh, Vinícius; Yokoyama, André; Ferro, Mariza; Schulze, Bruno (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
The performance evaluation in HPC, understanding the computational requirements of scientific applications, its relation with power consumption is a fundamental task to overcome the current barriers and to achieve the computational exascale. However, this imposes some challenging tasks, such as to monitor a wide range of parameters in heterogeneous environments, to enable fine grained profiling and power consumed across different components, to be language independent and to avoid code instrumentation. Considering these challenges, this work proposes the SMCis, an application monitoring system developed with the goal of to collect all these aspects in an effective and accurate way, as well as to correlate these data graphically, with the environment of analysis and visualization.